Adaptive design of tipping bucket flow meters for continuous runoff measurement - Schwamback, Dimaghi; Persson, Magnus; Berndtsson, Ronny; Anache, Jamil A. A.; Wendland, Edson Cezar (Frontiers in Environmental Science, 2023)
Introduction: Runoff measurement and monitoring is a laborious, time-consuming, and costly task. Additionally, common runoff monitoring usually primarily provide water level, requiring information on the stage-discharge relation. Automatic equipment such as flow meter tipping bucket (TB) is a potential option to simplify and provide continuous runoff monitoring in small catchments. However, a proper description of how to size and adapt the design under different flow conditions is still lacking. Methodology: In this paper we present a novel standardized framework for the design of TB that can be used for low-cost and real-time runoff monitoring under many different conditions. The framework consists of an estimation of the runoff peak rate using the rational equation and a volumetric capacity estimate of the cavity based on runoff rate, operation speed, and inclination angle of TB when at resting position. The proposed framework was implemented in a case study where four TBs were designed for continuous runoff monitoring from experimental plots (100 m2) with different land use (sugarcane, soybean, and bare soil). Results: During field tests (five months), the designed TBs had a recovery rate of actual runoff ranging from 61% to 81% and were able to capture features poorly studied (starting/ending time and peak flow) that have potential importance in hydrological models. Discussion: The proposed framework is flexible and can be used for different environmental conditions to provide continuous runoff data records.